Peculiarities of Silicon Nitride and Carbide Powder Synthesis - V. N. Kovalevsky; A. V. Kovalevskaya; V. V. Pytko (Наука и техника)
The paper shows that temperature, burning rate and content of main substance bear a relationship to nitrogen pressure in a reactor, charge density, blank diameter, specific surface of initial silicon powder at synthesis of Si3N4-SiC powder composition. It has been shown that control of synthesis conditions makes it possible to obtain Si3N4-SiC powder of the given composition and particle structure. During the synthesis process high-tensile disperse oc-SiC particles, a and p Si3N4 particles of hexahedral and octahedral shape with a size of 0.02...0.2 microns, P-Si3N4 particles of irregular shape and a-Si3N4 particles as fibres have been formed.